Steroids for LBP – from rationale to inconvenient truth (Swiss Medical Weekly, 2012)
Low back pain (LBP) and sciatica are highly prevalent and their treatment remains a clinical challenge. Systemic or local administration of corticosteroids is frequently prescribed for this indication, partly because its pathogenesis is believed to be a mix between mechanical and inflammatory phenomenon, and because corticosteroids do have some analgesic properties. Although there is some biological and animal data in favour of the use of corticosteroids in LBP and sciatica, clinical evidence remains scarce. Local epidural injection can have some short term benefit. However, we found no support for any type for systemic administration of corticosteroids, a practice that should definitively be banned.